IMPROVING THE PERFORMANCE OF CREW VESSEL PT. MARITIME BARITO PERKASA THROUGH SALARY SATISFACTION AND INCENTIVES - Yusuf, Muhammad; Setiawan, Lilik (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study was to determine and analyze the effect of salary satisfaction and incentives partially and simultaneously on the performance of employees of Crew Vessel PT. Maritim Barito Perkasa in Banjarmasin. This study is quantitative descriptive by testing 90 Crew Vessel respondents. Analysis of the data used is multiple linear regression analysis. The results showed that the salary satisfaction factor had a significant effect on the performance factors of Crew Vessel PT. Maritim Barito Perkasa in Banjarmasin. The factor of incentive satisfaction has a significant effect on the performance factor of Crew Vessel PT. Maritim Barito Perkasa in Banjarmasin. Simultaneously factors of salary satisfaction and incentive satisfaction significantly influence the performance factors of Crew Vessel PT. Maritim Barito Perkasa in Banjarmasin. Keyword: salary satisfaction, incentive, employee performance